Mechanical and microstructural characterization of Ti-SiC reinforced AA5083 surface composites fabricated via friction stir process. (24th December 2021) - Rahman, Md Ziyaur; Khan, Zahid A; Siddiquee, Arshad Noor; Abidi, Mustufa Haider; Aboudaif, Mohamed K; Al-Ahmari, Abdulrahman
Abstract: A mixture of Titanium and silicon-carbide powders was embedded in the AA5083 matrix by Friction Stir Processing (FSP). Experiments were performed as per Taguchi L8 orthogonal array, and the effect of reinforcement on hot strength (at 100 °C), processed zone (PZ) geometry, and microstructure were investigated. The effect of PZ geometry on the surface properties was also analyzed. The effect of heating the tensile test specimens to 540 °C on the strength at 100 °C was also separately investigated. It was observed that surface hardness was significantly enhanced by FSP, and the highest mean hardness of 90.4 HV was observed. Furthermore, it was observed that the surface properties also significantly depend on PZ geometry. From experimental results, it was found that the specimens with the lowest width to depth ratio bears the highest hardness and vice versa. A clear effect of parameters was evident on the geometry of processed zones with a deep bowl, and shallow cup-shaped zones were formed with smaller and larger shoulder diameters, respectively. The samples were processed at 355 rpm, 63 mm min −1, 17 mm shoulder, and 355 rpm, 80 mm min −1 . The 20 mm shoulder showed high tensile strength 292 MPa and 294 Mpa, respectively. The strength of these samples did not reduce much even after heating to 540 °C.